Intervensi Kognitif Terhadap Kecemasan Remaja Paska Erupsi Gunung Agung - I Nengah sumirta; IGA Ari Rasdini; i wayan candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
This study aims to prove the influence of there has been significant intervention cognitive against following the collapse of teenage angst phase of Agung mount, using the design of pra-eksperimental , the kind of research one-group pra-post test design in including on the instrument types .Sampling technique with a total the sampling method of , large 61 the sample Which is done based on data using the test and been approved paired t-test .There an effect there has been significant intervention cognitive against following the collapse of teenage angst phase of Agung mount the great with the value of p = 0,000 .